The effect of splint material rigidity in implant impression techniques - Del’Acqua, Marcelo Antonialli (2010)
Purpose: This in vitro study compared the dimensional accuracy of two impression techniques: Duralay splinted impression copings (D) and metal splinted impression copings (M) for implant-supported prostheses. Materials and Methods: A master cast with four parallel implant abutment analogs and a passive framework were fabricated. Vinyl polysiloxane impression material was used for all impressions with a metal stock tray. Two groups (D and M) were tested (n = 5). The measurement method employed was just one titanium screw tightened to the framework. Each group’s measurements were analyzed using software that received the images of a video camera coupled to a stereomicroscope at × 100 magnification. The results were analyzed statistically (t test). Results: The mean values of abutment/framework interface gaps were: master cast = 32 µm (SD 2), group D =165 µm (SD 60), and group M = 69 µm (SD 36). There was a statistically significant difference between the D and M groups (P = .001). Conclusion: Under the limitations of this study, it could be suggested that a more accurate working cast can be fabricated using metal splinted impression copings. © 2010 by Quintessence Publishing Co Inc.